2014
DOI: 10.1002/jcph.400
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury associated with ketoconazole: Review of the published evidence

Abstract: The azole antifungal agent ketoconazole has been available since 1981 for the treatment of fungal infections. In 2013, the American Food and Drug Administration and the European Medicines Agency issued warnings or prohibitions against the clinical use of oral ketoconazole due to the risk of liver injury which may lead to liver transplantation or death. From the available published evidence it is difficult to determine the actual incidence or prevalence of liver injury during clinical use of ketoconazole as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 89 publications
0
76
0
1
Order By: Relevance
“…Ketoconazole's side-effect profile (Table 1) is relatively benign, except for idiosyncratic severe hepatic dyscrasia, which is estimated to occur in one in 15 000 exposed individuals (115,(122)(123)(124). The FDA issued a black box warning for this in 2013, and the European Medicines Agency has restricted access to the agent to physicians specialized in treating CS (125).…”
Section: Evidence Ketoconazolementioning
confidence: 97%
“…Ketoconazole's side-effect profile (Table 1) is relatively benign, except for idiosyncratic severe hepatic dyscrasia, which is estimated to occur in one in 15 000 exposed individuals (115,(122)(123)(124). The FDA issued a black box warning for this in 2013, and the European Medicines Agency has restricted access to the agent to physicians specialized in treating CS (125).…”
Section: Evidence Ketoconazolementioning
confidence: 97%
“…Greenblatt et al demonstrated that approximately 1 in 500 patients were at risk of liver injury after ketoconazole administration. 14 In the early 1990s, when the triazoles became available for systemic use, they rapidly supplanted ketoconazole.…”
Section: Azolesmentioning
confidence: 99%
“…14 Unlike mammalian membranes, which are rich in cholesterol, ergosterol is the predominant sterol in the cell membrane of fungi. Thus, targeting ergosterol synthesis results in selectivity against fungi.…”
Section: Azolesmentioning
confidence: 99%
“…The FDA specifically recommended the use of clarithromycin or itraconazole as alternative strong CYP3A4/5 inhibitors for use in clinical DDI studies, but further noted that investigators may suggest other CYP3A4/5 inhibitors (FDA, 2013a). In addition to itraconazole and clarithromycin, ritonavir has also been suggested by some authors as a possible alternative to ketoconazole (Greenblatt and Greenblatt, 2014;Greenblatt, 2015;Greenblatt and Harmatz, 2015), but excluded by others on the basis of nonspecific CYP inhibition or induction (Ke et al, 2014;Liu et al, 2015).…”
mentioning
confidence: 99%